(untitled) (Jurnal Manajemen Bisnis, 2025)
This study examines the influence of Social Media Marketing (SMM), Perceived Luxury Value (PLV), and Consumption Status on Purchase Intention for luxury jewelry, with Generational Difference and Peer Influence as moderators. Gap analysis indicates that prior studies have rarely addressed how social media interactions, status consumption, and peer dynamics affect intergenerational purchasing behavior. A quantitative approach was employed using purposive sampling, with data from 400 respondents representing Generation Z and Millennials. Analysis with PLS-SEM reveals that SMM does not significantly affect Purchase Intention directly, although platforms such as Instagram and TikTok remain crucial as communication tools. In contrast, Consumption Status emerges as a dominant determinant of purchase decisions, highlighting the role of exclusivity and social recognition. Furthermore, Peer Influence strengthens the link between Consumption Status and Purchase Intention, particularly among Generation Z. Theoretically, this research contributes to luxury consumer behavior literature by underscoring the role of social value and peer mechanisms in bridging status consumption with purchase intention. Practically, the findings recommend that luxury jewelry marketers design digital strategies that emphasize luxury value while integrating peer influence and generational segmentation to enhance the effectiveness of social media campaigns.